STUDY OF THE DEVELOPMENT OF RURAL AREAS KULONPROGO DISTRICT (LOCATING A NEW GROWTH CENTER) - Lutfi Mutaali (Tunas Geografi, 2020)
This study aims to identify the dynamics of regional development and find a new growth center in Kulonprogo Regency which is based on rural areas. By using a quantitative analysis of regional development indicators, the results showed that out of 88 villages in Kulonprogo Regency, 19.4% had high and very high potential for regional development, supported by the availability of facilities and infrastructure, and also a high and very high centrality value, around 21.6%. These villages have the potential to be an embryo growth center with potential criteria high (17%) and very high (6.8%). The Chi-Square test and Pearson correlation show a close relationship between the factors that form the center of growth, such as population density and growth, level of regional development, availability of infrastructure, and the value of centrality. Four main urban centers (PUP) were selected, namely the villages of Pengasih, Wates, Giripeni, and Bendungan. The Center for Alternative Growth (PPA), namely Brosot, Sentolo, Jati Srono, Gerbosari villages. The rest will support the Alternative Growth Center, Airport Area, Aerocity, and rural hinterlands.Keywords: Regional development level, Growth center, Rural